Preschool Metacognitive Skill Assessment in Order to Promote Educational Sensitive Response From Mixed-Methods Approach: Complementarity of Data Analysis - Escolano-Pérez, Elena; Herrero-Nivela, Maria Luisa; Anguera, M. Teresa (Frontiers in Psychology, 2019)
A child's metacognitive skills contribute significantly to their learning and success. However, very few studies are focused on these skills at early education and most of them are carried out from inappropriate methodological perspectives for the characteristics of the youngest students. To overcome such limitations, it is essential carry out observational studies that analyze children's metacognitive behaviors in the natural and habitual context of children's learning, as well as appropriate tasks for their level of development. The aim of this study was to analyze the sequential and associative structure of the metacognitive skills used by 5-year-old children throughout the resolution of a playful task (a puzzle). It was interesting to know if there were different hidden structures in the use of metacognitive skills in the children who solved the puzzle and those who did not. From the methodological approach, this work was located in the perspective of mixed methods that are characterized by the integration of qualitative and quantitative elements. In this study this integration was be carried out from the "connect" option. This integration involved developing quantitizing, as one of its possibilities. Recent scientific literature has considered systematic observation, in which the QUALI-QUANTI-QUALI macro stages take place, as a mixed method itself. Consequently, systematic observation was applied, because it was suitable for our aim. A Nomothetic/Puntual/Multidimensional observational design was used. The playful activity of 44 pre-school children solving the puzzle individually was coded. It allowed us to obtain data matrices that respond to the QUALI stage. Regarding the QUANTI stage, once the quality of data was controlled, the records were further analyzed by differentiating two groups of participants (those who had solved the puzzle and those who did not) using three quantitative techniques of observational analysis (T-pattern detection, lag sequential analysis, polar coordinate analysis). Finally it was returned to a QUALI stage to interpret the results. The use of these three techniques allowed a detailed and in-depth analysis of children's activity. Results reveal differences in the metacognitive abilities of the children that solved and didn’t solve the puzzle. These results have important implications for educational practice.